Specificity of the Semantic Category of Graduality in Irish Folk Dance Terminology (London Journal of Research In Humanities and Social Sciences, 2025)
INTRODUCTION: The focus on cognitive aspects in the study of terminology of various domains makes it possible to address the mental capabilities of native speakers to explore their professional field and the world in general.The purpose of this study is to analyze the situation of terminological gradation in multicomponent terminological units operating in the English-language conceptual sphere of Irish folk dance, as well as to study the semantics of terminological graduality.In addition, the phenomenon of graduality in terminology has not been studied enough, although it is a fruitful material for research when the series of graded terms in the fields of special knowledge are clearly fixed in dictionaries and while functioning in the texts.METHODOLOGY AND SOURCES Scientists who studied the quantitative manifestations of grading processes in the semantics of general vocabulary units recognized the presence of special means of expressing graduality in the language (S.M. Kolesnikova, A.E. Levitsky, A.A. Krishtalyuk, etc.) The analysis was based on terms extracted by continuous sampling from explanatory terminological dictionaries, glossaries, original choreographic manuals and monographs on the history of dance over the period of about more than a hundred years.RESULTS AND DISCUSSION: The scale of graduality is based on the principles of changing one of the parameters perceived by a person (qualities, properties or quantities). Verbalization of a parameter change can be achieved through various linguistic means in multicomponent terminological units.Graded series of terms using examples of two- and three-component units, with the preliminary discussion of relevant information about the original single-component terms have been considered during the analysis.CONCLUSION: The conducted study of multicomponent English terms of Irish folk dance containing graded scales of various types allowed us to identify several aspects in specificity of the category of graduality. Thus, for example, grading quantifying term components explicate the progressive increase (decrease) of object characteristic features, the quantified “distance” during the transition from one specific feature to another. The sequence in essential features of the terminological nomination fixes the hierarchy of graded terms. 2000-2300
Keywords: Phenomenology; ASD; late modernity; complex phenomenon; psychotherapeutic discourse; medical discourse; psychotherapeutic discourse integrated into fiction; conceptual metaphor in therapy; agent and client of psychotherapeutic discourse; language representation of feelings and emotions.; existential psychoanalysis; Phenomenological clinic; Environmental devastation; Patriarchal Categories; Ecological Problem; Vandana Shiva.; distributive law; the right to deferred exchange; capital; the triad; the riddle of Varys; terminology; term; graded series of terms; graduality; terminological gradation.